RECONCILIATION MODEL OF TRANSPARENCY VALUE AND BUREAUCRACY SECRETION IN MANAGEMENT OF LOCAL GOVERNMENT BUDGET - PRADANA, I PUTU YOGA BUMI (Universitas Muhammadiyah Yogyakarta, 2015)
This study aims to present a reconciliation model of bureaucratic principles (Secretion) and democracy (Transparency) through the mapping of public information about managing a local government budget which is accessible to the public and which ones are excluded (secret) based on bureaucracy and public perceptions. This study uses a mixed method with sequential exploratory design and data collection research procedures using surveys, depth interviews, and documents. The validation data use source of triangulation techniques. The subjects of this study was divided into 2 (two) information assembling that is government bureaucracy and public Kupang determined by purposive. The results of this research showed that Kupang Goverment bureaucracy has 22 types of information perception (33,85%) in category information which is open and 42 types of information (64,62%) in category information that are closed while the public perceives 29 types of information (44,62%) in category information which is open and 26 types of information (40%) in the category of information that are closed. Therefore, to achieve the main of reconciliation to end of conflict between bureaucracy and public, later on the amount of information is open budget of management that are 32 types of information (49,2%) and the amount of information that is enclosed which includes 33 types of information (50,8 %) of the 65 types of management budget information by egulation No. 13 of 2006 on local Financial Management. KEYWORDS: Bureaucracy, Secretion, Transparency,Management of Local Government budget???????????????????????????????????????????????????????????????137